Tumor-Associated Macrophages: Therapeutic Targets for Skin Cancer - Fujimura, Taku; Kambayashi, Yumi; Fujisawa, Yasuhiro; Hidaka, Takanori; Aiba, Setsuya (Frontiers in Oncology, 2018)
Tumor-associated macrophages (TAMs) and regulatory T cells (Tregs) are significant components of the microenvironment of solid tumors in the majority of cancers. TAMs sequentially develop from monocytes into functional macrophages. In each differentiation stage, TAMs obtain various immunosuppressive functions to maintain the tumor microenvironment (e.g., expression of immune checkpoint molecules, production of Treg-related chemokines and cytokines, production of arginase I). Although the main population of TAMs is immunosuppressive M2 macrophages, TAMs can be modulated into M1-type macrophages in each differential stage, leading to the suppression of tumor growth. Because the administration of certain drugs or stromal factors can stimulate TAMs to produce specific chemokines, leading to the recruitment of various tumor-infiltrating lymphocytes, TAMs can serve as targets for cancer immunotherapy. In this review, we discuss the differentiation, activation, and immunosuppressive function of TAMs, as well as their benefits in cancer immunotherapy.